Chlorido(chlorodifluoroacetato-κO)bis(1,10-phenanthroline-κ2N,N′)manganese(II) - Seik Weng Ng; Kong Mun Lo (Acta Crystallographica Section E, 2008)
The chloride and chlorodifluoroacetate anions occupy cis positions in the octahedral coordination geometry of the title compound, [Mn(C2ClF2O2)Cl(C12H8N2)2]. The two N-heterocycles both chelate the metal atom.